The Use Of E-Reservation Open-Source Software (OSS) On Web-Based Laboratory Scheduling Information Systems In Order To Support Education Laboratory Management - Nurul Syamsiah (Universitas Muhammadiyah Tangerang, 2021)
Good laboratory management is needed to improve laboratory efficiency and effectiveness; one component of laboratory management is the use of laboratories. Laboratory use problems arise when there is a schedule change or a schedule conflict occurs since the management is still done manually, causing long automation and the lack of information on the laboratory’s availability, this can certainly hamper teaching and learning activities in the laboratory. To overcome this, it is necessary to have a system which can provide information on the availability of an effective laboratory and faster automation, one of which is by using the open-source software e-Reservation Meeting Room Booking System. It is a PHP and MySQL-based room reservation information system that can be used for laboratory scheduling and providing information on laboratory availability.